2022
DOI: 10.1002/aelm.202101389
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Activation Energy Mapping and Leveraging for Accelerating Ferroelectric Domain Nucleation and Growth

Abstract: The dynamics of ferroelectric domain switching are directly mapped in a PbZr0.2Ti0.8O3 thin film using piezoresponse force microscopy. Employing the rastering tip as a poling electrode to locally apply a fixed bias near the coercive field, while simultaneously monitoring the evolving domain pattern during continuous imaging, the effectively independent switching dynamics for numerous domains are directly investigated. While areal poling follows the anticipated S‐curve, this is shown to be the collective outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Recent work from Nath et al reported n 4 4 values for select regions of epitaxial PZT thin films via scanning probe and connected the large n values with a lack of existing nucleation sites, but further mechanistic discussion was limited. 25 The extended model demonstrated in this work rationalizes the phenomena of such rapid transitions via characteristic nucleation and growth times and is also applicable to the nucleation-growth mechanism in crystallization processes beyond ferroelectric switching.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Recent work from Nath et al reported n 4 4 values for select regions of epitaxial PZT thin films via scanning probe and connected the large n values with a lack of existing nucleation sites, but further mechanistic discussion was limited. 25 The extended model demonstrated in this work rationalizes the phenomena of such rapid transitions via characteristic nucleation and growth times and is also applicable to the nucleation-growth mechanism in crystallization processes beyond ferroelectric switching.…”
Section: Discussionmentioning
confidence: 70%
“…3a and b), conceptually consistent with Merz's law 46 and in a manner similar to comparable studies on perovskite oxide ferroelectric thin films. 19,25,47 In addition to the shift, the slope of the polarization increase steepens with increasing applied electric field for both materials. This slope change is also seen in conventional ferroelectrics, 19,47 though only the recent study from Nath, et al , has reported n values >3.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations